Pengaruh Obat Kumur Mengandung Alkohol 9% Dan Non-Alkohol Terhadap Kekuatan Tekan Resin Komposit Bulk-Fill (Penelitian) - Gabriella Sun; Dewi Liliany Margaretta (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Background: Bulk-fill composite resin is a tooth-colored restoration material that is developed to obtain better aesthetic and mechanical properties, which include compressive strength. The factors influencing the reduction of compressive strength of composite resin are hydrophilic matrix monomers and inadequate bonds between compositions. One of the absorbable liquids is a mouthwash commonly used to control dental caries and reduce the amount of plaque after brushing the teeth. Objective: To determine the effect of mouthwash containing 9% alcohol and nonalcohol on the compressive strength of bulk-fill composite resin. Method: The research type conducted is an experimental laboratory. The compressive strength of bulk-fill composite resin will be tested using Universal Testing Machine. There were three treatment groups, which are immersion in mouthwash containing 9% alcohol, nonalcohol, and artificial saliva as a control group. Samples were immersed at room temperature 25°C for 12 hours according to instructions for use twice a day for 30 seconds. Results: The One Way ANOVA test shows a significant value, which was sig. 0.001 (p < 0.05). There were significant differences in the test of the effect of mouthwash containing 9% alcohol and nonalcohol mouthwash on the compressive strength of bulk-fill composite resin. This result is caused by the hydrophilic traits of the matrix monomers, mechanisms that occur in resin compositions, acidity and alcohol content of mouthwash can affect the reduction in compressive strength of the composite resin. Conclusion: The mouthwash containing 9% alcohol reduced the compressive strength of bulk-fill composite resin more compared to nonalcohol mouthwash.